2018
DOI: 10.1002/cbic.201700648
|View full text |Cite
|
Sign up to set email alerts
|

Altering 2‐Hydroxybiphenyl 3‐Monooxygenase Regioselectivity by Protein Engineering for the Production of a New Antioxidant

Abstract: 2-Hydroxybiphenyl 3-monooxygenase is a flavin-containing NADH-dependent aromatic hydroxylase that oxidizes a broad range of 2-substituted phenols. In order to modulate its activity and selectivity, several residues in the active site pocket were investigated by saturation mutagenesis. Variant M321A demonstrated altered regioselectivity by oxidizing 3-hydroxybiphenyl for the first time, thus enabling the production of a new antioxidant, 3,4-dihydroxybiphenyl, with similar ferric reducing capacity to the well-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…266 A more recent study showed that HbpA M321A catalyzes selective C-4 hydroxylation of 3-hydroxybiphenyl (240), a substrate not accepted by wild-type HbpA (Scheme 42A). 267 The 4-hydroxyphenylacetate 3-hydroxylases (HPAHs) are two component FMOs that natively catalyze hydroxylation of 4-hydroxyphenylacetate to 3,4-dihydroxyphenylacetate and accept a range of additional substrates. 268 The S146A variant of HPAH from Acinetobacter baumannii provides improved activity on 4-aminophenylacetic acid to give 3-hydroxy-4-aminophenylacetic acid when compared to wild-type.…”
Section: Scheme 41 Catalytic Cycle For Hydroxylation Of a Phenolic Co...mentioning
confidence: 99%
“…266 A more recent study showed that HbpA M321A catalyzes selective C-4 hydroxylation of 3-hydroxybiphenyl (240), a substrate not accepted by wild-type HbpA (Scheme 42A). 267 The 4-hydroxyphenylacetate 3-hydroxylases (HPAHs) are two component FMOs that natively catalyze hydroxylation of 4-hydroxyphenylacetate to 3,4-dihydroxyphenylacetate and accept a range of additional substrates. 268 The S146A variant of HPAH from Acinetobacter baumannii provides improved activity on 4-aminophenylacetic acid to give 3-hydroxy-4-aminophenylacetic acid when compared to wild-type.…”
Section: Scheme 41 Catalytic Cycle For Hydroxylation Of a Phenolic Co...mentioning
confidence: 99%
“…Fishman et al. produced the HbpA variant, M321A, through saturation mutagenesis studies, which displayed altered regioselectivity and activity [89] . M321A catalysed hydroxylation of non‐natural substrate 3‐hydroxybiphenyl ( 7 ) to produce a new antioxidant, 3,4‐hydroxybiphenyl ( 8 ) (Figure 3A) [89] …”
Section: Oxygenating Biocatalystsmentioning
confidence: 99%
“…[88] Fishman et al produced the HbpA variant, M321A, through saturation mutagenesis studies, which displayed altered regioselectivity and activity. [89] M321A catalysed hydroxylation of non-natural substrate 3-hydroxybiphenyl (7) to produce a new antioxidant, 3,4-hydroxybiphenyl (8) (Figure 3A). [89] Unlike single-component monooxygenases, which have only been reported to use FAD as a cofactor, two-component monooxygenases can either use reduced FAD or FMN.…”
Section: Flavin-dependent Monooxygenasesmentioning
confidence: 99%
See 1 more Smart Citation
“…3-hydroxybenzoate 4-hydroxylase (3HB4H; EC 1.14.13.23) and 3-hydroxybenzoate 6-hydroxylase (3HB6H; EC 1.14.13.24). The aromatic hydroxylase 2-hydroxybiphenyl 3-monooxygenase (HbpA; EC 1.14.13.44) has been studied extensively for applied biocatalysis (Scheme 7.2a) [36][37][38]. An important hydroxylation reaction catalyzed by several group A enzymes concerns the ipso-attack [46].…”
Section: Group a Reactionsmentioning
confidence: 99%